1996
DOI: 10.1128/jb.178.21.6394-6398.1996
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of exochelins of Mycobacterium avium: evidence for saturated and unsaturated and for acid and ester forms

Abstract: Mycobacterium avium secretes iron-binding siderophores called exochelins. The exochelins from M. avium have previously been reported to have unsaturated side chains that terminate in carboxylic acid. In contrast, our data show the side chains to be both saturated and unsaturated and to terminate with either a carboxylate or methyl ester.Mycobacterium avium is a slowly growing mycobacterium and an important human pathogen. Because M. avium is one of the most common opportunistic pathogens associated with AIDS, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
38
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 12 publications
0
38
1
Order By: Relevance
“…The same research group also showed that coupling of high-performance liquid chromatography (HPLC) with ESI MS is an effective strategy for separation and identification of siderophores in complex samples [19]. Gibson and coworkers applied MS/MS to characterize exochelin siderophores and found that its side chains are both saturated and unsaturated and terminated with either a caboxylate group or a methyl ester [11,21]. These results contrasted with the previous observation that exochelins are unsaturated and terminated with carboxylic acid [16].…”
contrasting
confidence: 55%
See 1 more Smart Citation
“…The same research group also showed that coupling of high-performance liquid chromatography (HPLC) with ESI MS is an effective strategy for separation and identification of siderophores in complex samples [19]. Gibson and coworkers applied MS/MS to characterize exochelin siderophores and found that its side chains are both saturated and unsaturated and terminated with either a caboxylate group or a methyl ester [11,21]. These results contrasted with the previous observation that exochelins are unsaturated and terminated with carboxylic acid [16].…”
contrasting
confidence: 55%
“…Electrospray ionization mass spectrometry (ESI MS) and tandem mass spectrometry (MS/MS) have proved to be powerful techniques for detecting and identifying siderophores [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. For example, Gledhill demonstrated the utility of these techniques for characterizing hydroxamate-type siderophores, including ferrioxamine, ferrichrome, and iron(III) rhodotoluate [9].…”
mentioning
confidence: 99%
“…Iron, essential for pathogen survival, is sequestered from its host by well-characterized siderophore-mediated iron acquisition pathways. Pathogenic mycobacteria including Mtb synthesize two types of siderophores-the cell-bound water-insoluble mycobactins and the secreted water-soluble exochelins, which have a mycobactin-like backbone (1,2), and are referred to as exomycobactins hereafter. Exomycobactins, the most abundant molecules secreted by Mtb on a molar basis, can remove iron from human transferrin and lactoferrin and transport it to either mycobactins in the Mtb cell wall (3) or the iron transport system, IrtA/B (4).…”
mentioning
confidence: 99%
“…Calder and Horwitz showed the iron-regulated expression of Irp10 and Mta72 in Mycobacterium tuberculosis by single-dimension electrophoresis (3) and later, using two-dimensional gel electrophoresis combined with mass spectrometry and sequence information (27), demonstrated the upregulation of a putative cation transporting ATPase, a mycobacterial homologue of phosphoenolpyruvate carboxykinase, and an NADPdependent dehydrogenase in bacteria grown in low-iron medium, whereas these authors observed increased levels of FurA, a homologue of EF-Tu, and an aconitase in iron-rich medium.…”
mentioning
confidence: 99%